When school operates in the awareness of young teenagers in the fight against STDs - Silva, Renan da [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2015)
The aim of this study was to contribute to the teaching of Sexually Transmitted Diseases (STDs) in High Schools. The study was done from the research knowledge about STDs of 61 students from two schools of Rio Claro, SP: a state and a private school, through a questionnaire (Pre-test) and an interview with two Biology professors, each one from each school. The results indicated that, in general, the students in the private school had more knowledge about the subject. The public school students showed more problems with knowledge (knowledge or information?) about the symptoms of STDs. In those two schools the knowledge on the subject proved to be generic and superficial. According to the Biology teachers, both of them teach about the content and the teaching material contains themes of sexuality and STDs. From these results, an intervention was developed with students, using methods such as group dynamics and lecture dialogued lessons. After the intervention, there was an increase in the percentage of correct answers for the students of both schools (Post-test) which shows that it was effective. We conclude that this work has achieved its goal to enlighten students on the topic, but schools fail to have a better dialogue with their students for the planning of such content, since although its teaching is expected, learning is not happening as expected.
Keywords: adolescents; STDs; education and health; sexual education; High School